DEVELOPING ADOBE FLASH PROFESSIONAL AS A LEARNING MEDIA TO INCREASE THE FIRST GRADE STUDENTS` SPEAKING ACHIEVEMENT AT JUNIOR HIGH SCHOOL IN THE 2018/2019 ACADEMIC YEARS - Yunia Wulandari; Dian Fadhilawati (JOSAR (Journal of Students Academic Research), 2019)
The research was Research and development which intended to develop a valid and effective model of Adobe Flash Professional as a Learning Media to Increase the First Grade Students’ Speaking Achievement at Junior High School especially on the topics Greeting and leave taking as well as apologizing.This reseacrh applied Research and Development (R&D) design, based on Sugiyono model.which include : Analyzing potential and problem, Data collection, Product design, Product validation, Product revision, Product testing/try-out, Product revision and Final product. The subject of this research were 29 students of VII C in MTs Ma’arif NU GandusariBlitar. The data of the research were quantitative data ( the result from Test and Questionnaire) and qualitative ( the result of interview)The result of the research showed that: (1) The developed product (adobe flash profesional) as a learning media was valid, it was proved by the result of content English material validation (77.4%) and media validation (70.4%); (2) Developed Adobe flash professional as a learning mediawas effective to increase the first grade students’ speaking achievement, it was proved by the increasement of the students’ speaking mean score of Greeting and Leave Taking from (43.40) to (80.50) and score of Apologizing from (45.00) to (91.70); (3) Students gave positive responses toward the developed adobe flash professional as a learning media in teaching speaking reflected from the result of questionnire given (80.80%). From the result above, it can be concluded that adobe flash professional as a learning media was valid to be applied in teaching learning and effective to increase the first grade students’ speaking achievement at MTs Ma’arif NU GandusariBlitar.